Superantigenic activity of emm3 Streptococcus pyogenes is abrogated by a conserved, naturally occurring smeZ mutation. - Claire E Turner; Mary Sommerlad; Karen McGregor; Frances J Davies; Bruno Pichon; Deborah L W Chong; Leili Farzaneh; Matthew T G Holden; Brian G Spratt; Androulla Efstratiou; Shiranee Sriskandan (PLoS ONE)
Streptococcus pyogenes M/emm3 strains have been epidemiologically linked with enhanced infection severity and risk of streptococcal toxic shock syndrome (STSS), a syndrome triggered by superantigenic stimulation of T cells. Comparison of S. pyogenes strains causing STSS demonstrated that emm3 strains were surprisingly less mitogenic than other emm-types (emm1, emm12, emm18, emm28, emm87, emm89) both in vitro and in vivo, indicating poor superantigenic activity. We identified a 13 bp deletion in the superantigen smeZ gene of all emm3 strains tested. The deletion led to a premature stop codon in smeZ, and was not present in other major emm-types tested. Expression of a functional non-M3-smeZ gene successfully enhanced mitogenic activity in emm3 S. pyogenes and also restored mitogenic activity to emm1 and emm89 S. pyogenes strains where the smeZ gene had been disrupted. In contrast, the M3-smeZ gene with the 13 bp deletion could not enhance or restore mitogenicity in any of these S. pyogenes strains, confirming that M3-smeZ is non-functional regardless of strain background. The mutation in M3-smeZ reduced the potential for M3 S. pyogenes to induce cytokines in human tonsil, but not during invasive infection of superantigen-sensitive mice. Notwithstanding epidemiological associations with STSS and disease severity, emm3 strains have inherently poor superantigenicity that is explained by a conserved mutation in smeZ.